Tailored twist morphing achieved using graded bend–twist metamaterials - Javad Taghipour (Composite Structures, 2022)
This work develops a morphing concept that utilises a metamaterial as the passive morphing device for helicopter blades. The metamaterials are created with bend–twist coupling, which enable the blade twist under prescribed bending loads. Finite element analysis (FEA) is performed to investigate the influence of the unit cell configurations on the coupling properties of the metamaterials. The numerical models are then validated experimentally through a set of bending tests conducted with additively manufactured prototypes. Finally, the validated model is used to design a graded metamaterial, where the cell aspect ratio gradually changes along the blade span, providing unique bend–twist coupling and allowing for tailored twist to be obtained. The results suggest the graded metamaterials are capable of introducing optimised nonlinear twists to the blade during different flight conditions including both hover and forward flight.